1995
DOI: 10.1002/mrd.1080410203
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gene expression in the preimplantation mouse embryo by TGF‐α and TGF‐β

Abstract: The effect of growth factors on regulating gene expression in the preimplantation mouse embryo was examined, since results of previous experiments revealed a stimulatory effect of exogenously-added growth factors on preimplantation development in vitro. Treatment of early cavitating blastocysts with either 250 pM TGF-alpha or TGF-beta results in changes in the pattern of total protein synthesis as assessed by high-resolution two-dimensional gel electrophoresis. In some cases, the synthesis of a particular poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…We also found transforming growth factor beta regulator 1 (TBRG1), a growth inhibitory protein induced in cells undergoing arrest in response to DNA damage and TGF-β1 [54], was more highly expressed in Pkd1flox/flox; Ksp-Cre mice than in matched wild type mice on the 1st day after birth in our proteomics study (data not shown). Further studies are needed to clarify the complex cross-talk between the cAMP-PKA and TGF-β-activated pathways in PKD.…”
Section: Discussionmentioning
confidence: 88%
“…We also found transforming growth factor beta regulator 1 (TBRG1), a growth inhibitory protein induced in cells undergoing arrest in response to DNA damage and TGF-β1 [54], was more highly expressed in Pkd1flox/flox; Ksp-Cre mice than in matched wild type mice on the 1st day after birth in our proteomics study (data not shown). Further studies are needed to clarify the complex cross-talk between the cAMP-PKA and TGF-β-activated pathways in PKD.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have implicated a variety of putative growth factors including platelet-activating factor (PAF) [4], insulin-like growth factor I (IGF-I) [5,6], IGF-II [7], and epidermal growth factor/transforming growth factor ot [8,9]. Their mechanisms of action and their temporal pattern of action is poorly understood, while the very nature of autocrine mediators (produced by and acting on the same cell populations) make such studies difficult.…”
Section: Introductionmentioning
confidence: 98%
“…During preimplantation development, many of these factors and their receptors are also expressed in the embryos. Addition of growth factors to the culture medium facilitates embryo development [5][6][7], suggesting that paracrine pathways exist between the oviduct and the preimplantation embryos.…”
Section: Introductionmentioning
confidence: 98%